History Matters: Racialized Motherhoods and Neoliberalism. Issue 3 (17th July 2020) - Toft, Jessica
Abstract: Neoliberal political reasoning is remaking the state's democratic character and its governing rules to reflect those of the market. The most prominent legislative example, Temporary Assistance for Needy Families, dictates work requirements, time limits, and monitoring and sanctioning of clients. Through such policies, the primary aims of government assistance changed from aiding needy citizens to transforming individuals into paid workers, regardless of continued poverty or care obligations. Although scholarship of related policy and governance tools has grown, less study has centered on understanding the historic events and ways in which race-based, gendered, and poverty narratives facilitated adoption of such austere policies. This article compares circumstances of African American and White mothers in the United States from the Revolutionary War to the postwelfare era. It describes what neoliberalism is, discusses the role of ideological discourses in policy and governance, presents the history and historical racialized portrayals of White and African American motherhood during this period, and analyzes the differential impact of ideological discourses using a lens of intersectionality. The conclusion discusses how discriminatory discourses subvert a democratic ethos for all and suggests ways for social workers to contest the impacts of neoliberalism.